Effect of ball sizes on synthesis of OsB2 powders by mechanical alloying. Issue 18 (15th December 2017) - Zou, Canhui; Long, Ying; Zheng, Xin; Lin, Hua-Tay; Zhang, Fenglin
Abstract: In present study, OsB2 powders were synthesized by mechanical alloying (MA) using high energy ball milling technique. Milling balls with different sizes (6.5 mm, 9.5 mm, 11.5 mm, and mixture of 3 ball sizes) were used with other milling parameters unchanged. The effects of ball sizes on synthesis process of the OsB2 powders were studied. Phase identification, morphology and particle size of the mixed powders synthesized by balls with different sizes under different milling time were performed by X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM), respectively. Results show that the main phase of the as-synthesized powders are ReB2 -type hexagonal OsB2 obtained for the four groups of milling balls with different sizes. But the synthesis efficiency of OsB2 powders increases with the decrease of ball sizes. With ball diameter of 6.35 mm (the smallest size), the main phase in the as-synthesized powder is ReB2 -type hexagonal OsB2, whereas mixture of hexagonal and orthogonal OsB2 powders are obtained with other three groups of balls. The different in synthesis efficiency and phase composition of the powders could be attributed to the varied total energy generated during the collision process and the surface area of the balls with different ball sizes.